Antarctica - Robinson, Kim Stanley 1952- (Bantam Books, 1998)
Eco-terrorists battle capitalists, seeking to open Antarctica to commercial exploitation. The time is the 21st century, the world is an ecological disaster, and the treaty banning mineral exploration of Antarctica has expired. By the author of Red Mars.
Keywords: Ökologie; Ecology -- Antarctica -- Fiction; Mineral resources conservation -- Antarctica -- Fiction; Science fiction.; Antarctica -- Fiction; Antarktis; Fiktionale Darstellung; Adventure fiction; Science fiction